1966
DOI: 10.1002/ar.1091550403
|View full text |Cite
|
Sign up to set email alerts
|

An engineering analysis of myocardial fiber orientation in pig's left ventricle in systole

Abstract: The concept of discrete layers and bundles of muscle as a basic structural arrangement in left ventricular myocardium was tested by measuring the helix angles at 1 m m intervals from endocardium to epicardium, using pig's heart in the contracted state. A fixed coordinate system was established which permitted measurement of corresponding sites in hearts of different dimensions.The helix angle was found to change from somewhat less than 90" endocardially to about -90" epicardially in a n almost linear clockwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
119
2
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 5 publications
16
119
2
1
Order By: Relevance
“…Thus, we used diffusion tensor magnetic resonance imaging to trace the primary diffusion vectors of the myocardium so as quantitatively to assess the overall orientation of the myocytes within different regions of the ventricular walls. We found the helical angle to change at different depths within the walls as established for the left ventricle, and as previously shown with histological techniques (Greenbaum et al, 1981), with endocardial myocytes aggregated so as to form right hand helical patterns, and epicardial myocytes aggregated as left hand helixes (Pettigrew, 1864;Streeter et al, 1966;Streeter et al, 1969;Schmid et al, 2005). Significantly, we were able to identify virtually identical myocardial tracks in hearts with or without hypertrophy, showing that the right ventricular wall is arranged in reproducible composites of aggregated myocytes, as has also been observed in the left ventricle (Smerup et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, we used diffusion tensor magnetic resonance imaging to trace the primary diffusion vectors of the myocardium so as quantitatively to assess the overall orientation of the myocytes within different regions of the ventricular walls. We found the helical angle to change at different depths within the walls as established for the left ventricle, and as previously shown with histological techniques (Greenbaum et al, 1981), with endocardial myocytes aggregated so as to form right hand helical patterns, and epicardial myocytes aggregated as left hand helixes (Pettigrew, 1864;Streeter et al, 1966;Streeter et al, 1969;Schmid et al, 2005). Significantly, we were able to identify virtually identical myocardial tracks in hearts with or without hypertrophy, showing that the right ventricular wall is arranged in reproducible composites of aggregated myocytes, as has also been observed in the left ventricle (Smerup et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…with as low a radius of curvature as possible (Krehl L, 1891). Although the measured helical angles of the aggregated right ventricle myocytes are similar to those found in the walls of the left ventricle (Streeter et al, 1966;Streeter et al, 1969), this is because we measured these angles relative to the long axis of the left ventricle, choosing this axis because of its consistent geometry between hearts when compared to the more complex right ventricular geometry. In this light, it is of interest to study the situations in which the right ventricle faces an increase in afterload so as to assess whether the fundamental morphological differences allow adaptation.…”
Section: The Functional Implications Of the Similarities In Left-and mentioning
confidence: 95%
See 1 more Smart Citation
“…The architectural complexity of the myocardium and the potential role that the ECM played in maintaining unique myocyte orientations throughout the LV free wall were described by Streeter and Basset (417,418). Using a structural engineering approach, these authors demonstrated that myocyte orientation and myocardial fiber angles were highly organized and moved in a continuous fashion from the endocardium to the epicardium.…”
Section: A Structure and Function Of The Myocardial Matrixmentioning
confidence: 99%
“…These anisotropies are derived from the variable distributions of cardiac fiber orientations. 39,40 This method utilized the DTI-based fiber orientations to simulate the anisotropic effects by processing the point scatterers with an ellipsoidal filter. Although different angles between fiber orientations and ultrasound beam directions lead to different intensities, the proposed simulation method can model these differences of myocardial intensities as the real imaging does.…”
Section: Discussionmentioning
confidence: 99%